The Effect of Lingua Franca (Persian) on Minority Languages (Kurdish) - Saiedi, Mahnaz; Rezvani, Payman (Mediterranean Journal of Social Sciences, 2012)
The present study aims to consider the effect of lingua franca a sample of which is Persian upon minority languages asKurdish which is spoken in a place where both Azari and Kurd-ish people have to communicate but by means of a third language(Persian) .the lexicon ,syntactical and phonological features of Kurdish in the local areas based on gathered data have beenstudied. The data gathered by questionnaire and recorded sounds along with in-terview with the local people, in particular literateones who had the greatest exposure to the third language (lingua franca). The researcher could find significant changes whichwere traced to the impact of Persian as lingua franca in the region. This research is an innovation in its own kind and helps thosewho follow lingua franca and language changes and try to find any relations of which with linguistic purposes as well as languageteaching.